2005
DOI: 10.1007/s10704-005-6033-x
|View full text |Cite
|
Sign up to set email alerts
|

Radial Fracture During Indentation by Acute Probes: II, Experimental Observations of Cube-corner and Vickers Indentation

Abstract: International Journal of Fracture (2005) 136:265-284Abstract. The companion article proposed a model for radial crack development at sharp contacts. The major extension of this model from previous works is the inclusion of a 'wedging' mechanism, to form a three-stress-field description of indentation crack evolution. Here, the amplitude terms of the three stress-intensity factors comprising the model are calibrated from experimental in situ and post situ inert-environment radial crack measurements on soda-lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…However, when the indenter edges come into contact with the surface the stress concentration effect magnifies the local stresses and, at a critical load, cracking starts and propagates through the coating following the edge of the indenter which is in contact with it. The edge of the indenter causes a wedging effect opening the crack [11,12]. As the load increases the crack can extend, but is constrained within the impression by the substrate plastic deformation.…”
Section: Analysis Of the Load-displacementmentioning
confidence: 99%
“…However, when the indenter edges come into contact with the surface the stress concentration effect magnifies the local stresses and, at a critical load, cracking starts and propagates through the coating following the edge of the indenter which is in contact with it. The edge of the indenter causes a wedging effect opening the crack [11,12]. As the load increases the crack can extend, but is constrained within the impression by the substrate plastic deformation.…”
Section: Analysis Of the Load-displacementmentioning
confidence: 99%
“…1 In the case of h, chipping experiments with a Vickers indenter on various ceramics revealed that h ¼ 9.3 [9]. As shown by [21], however, this coefficient is strongly (and subtly) affected by the pyramid angle f. The case of spherical chipping is more involved, and is differed to future work. The coefficients so determined are listed in Table 1.…”
Section: Evaluation Of Coefficientsmentioning
confidence: 86%
“…where c is the crack length (according to Figure 9), and is an indenter constant, which for example is 0.0161 for a Berkovich indenter [44]. For such small scales, the load required to crack the material using a Vickers probe is impractical, so a cube-corner probe is often used instead, which lowers the cracking load threshold [89]. While hardness is traditionally assumed to be independent of load applied, care should be taken to indent the material sufficiently enough to prevent the phenomenon of the indentation size effect from providing accurate measurements of the particle [86].…”
Section: Nanoindentationmentioning
confidence: 99%